Inovasi Produk, Kreatifitas Iklan Dan Brand Trust Mendorong Keputusan Pembelian - Santoso, Rudi; Erstiawan, Martinus Sony; Kusworo, Angen Yudho (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This research was conducted to reveal consumer behavior in terms of smartphone purchase decisions. The study tries to reveal consumer behavior in terms of deciding on product purchases, especially OPPO brand smartphones. The level of brand trust, innovation, ad creativity, and ad effectiveness are thought to influence consumer decisions in purchasing OPPO brand smartphones. The results showed that Product Innovation (X1), Ad Creativity (X2) and Ad Effectiveness (X3) had a significant effect with each value of β being 0.091; 0.589; and 0.580. Meanwhile Brand Trust (X4) has a negative effect on purchasing decisions. R2 value indicates 0.673, which means that the four variables simultaneously influence 67.3% of the purchasing decision (Y).